THE COMBINATION OF EDUCATIONAL AND WORK ACTIVITIES AS A REALIZATION OF THE YOUTH'S DESIRE FOR ECONOMIC SEPARATION - Bahrii, Hanna; Кolomoiets, Olena; Nedilko, Kateryna (SWorld-Ger Conference proceedings, 2024)
The work considers the combination of educational and work activities as a key factor in realizing the youth's desire for economic independence. Dual education in the European Union and its implementation in Ukraine are analyzed, attention is focused on t